A Study Of Career Suitability Among Medical Students - Nurul Azmawati Mohamed @ Abd Aziz; Zarini Ismail; Nur Syahrina Rahim; Shalinawati Ramli; Nurul Hayati Chamhuri; K. Omar; Nurul Azmawati Binti Mohamed @ Abd Aziz; Zarini Ismail; Shalinawati Ramli; Nurul Hayati Chamhuri; Nur Syahrina Rahim; K. Omar (World Academy of Science, Engineering and Technology, 2024)
Choosing a career is one of the most important decisions in our life. A right career leads a person to grow with that career and achieve success through the decision. Thus, career suitability assessment is important to help individuals to understand how a variety of personal attributes can impact their potential success and satisfaction with different career options and work environments. Some career needs specific personality trait that relates to attributes of job requirements and commitments. For medicine, being caring, approachable, inquisitive, able to listen and understand patients’ pain, anxiety and sorrow are important. The aim of this study was to evaluate the career suitability of pre-clinical students. This was a cross sectional study conducted among pre-clinical medical students in Universiti Sains Islam Malaysia. 'Sidek Career Interest Inventory’ was used to assess the students’ suitability for the course. This instrument had been validated locally to suit the local social and cultural context. It assessed the students’ personality trait based on Holland’s theory and their interests. For students to pursue in the medical course, two main personality trait are believed to be essential namely investigative and social trait personalities. Some of the characteristics of investigative trait are analytical, rational, intellectual and curious, while the characteristics of social trait personality include empathy, friendly, understanding and accommodating. The score for each personality trait were categorized as low (0-3.99), moderate (4-6.99) and high (7-10). A total of 81 pre-clinical medical students were included in this study. About two third (93.8%) of them were female and all of them are from 20 to 21 of age. Approximately, half of the students (47.5%) scored high and another 46.3% scored moderate for investigative trait. For social trait, only 13.8% scored high while 31.3% scored moderate. Only 12.5% (10) students had high scores for both investigative and social traits. Most of the pre-clinical medical students scored high in the investigative sections, however their social values were inadequate (low scores). For them to become good medical doctors, they should be good in both investigative and social skills to enhance their suitability for this career. Therefore, there is a need to nurture these medical students with appropriate social values and soft skills.